Elaborasi Pemanfaatan Proteksi Jaminan Bagi ASN Aktif Dan Pensiun Pada PT Taspen (Persero) Kantor Cabang Surakarta Jawa Tengah - Siska Oktaviany; Wahyudiyono; Khoiri Najib; Moh. Sholihin (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2025)
Each individual has an age limit so that they cannot work and enjoy their old age. PT TASPEN (Persero) is a State-Owned Enterprise authorized to manage the State Civil Apparatus (ASN) pension fund. This study discusses the use of guarantee protection for active and retired civil servants at PT TASPEN Surakarta. The method used is qualitative which is presented in narrative form. The resource persons taken in this study amounted to 3 informants with details of 2 HC (Human Capital) And GA (General Affairs) Staff and 1 HC (Human Capital) And GA (General Affairs) Sector Head Surakarta. The result is that TASPEN Surakarta has four guarantee programs, namely the ENT Program (Old Age Savings), Pension Program, JKK Program (Work Accident Insurance) and JKM Program (Death Insurance) which can be claimed online through TASPEN's TOOS, payment partners or through the nearest branch office. The benefits that will be obtained by participants are insurance in case of work accidents, continuous pensions, death bereavement money, and scholarships for children. However, in reality there is one program that has not been understood by participants, namely Work Accident Insurance (JKK), this can be seen from the number of active civil servants who have not taken advantage of this program when they are disabled and die due to work accidents.